INNOVATIVE SETTINGSVOJLANISH CONDITIONS OF ENTERPRISES IN THE ACTIVITIES OF THE STRATEGIC MANAGEMENT EFFICIENCY - Bakhtiyor Tukhliyev (Web of Journals Publishing, 2025)
This article examines the effectiveness of the strategic management of the enterprise, the factor affecting the dog, the issues of improving the competitiveness of the enterprise and the increasing metho in the organization and economic management mechanism.
Keywords: Strategic management, enterprise activity, innovative integration indicators, strategy, estimation, sustainability of the enterprise.